Hubungan Dukungan Sosial dan Kesejahteraan Subjektif pada Mahasiswa - Alfina Rizky Damayanti; Lucky Purwantini (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the relationship between social support and subjective well-being among students at Universitas Islam 45 Bekasi. College students, transitioning from adolescence to adulthood, often face academic pressures and life challenges impacting their well-being. This study use a quantitative correlational design and involved 134 students selected through simple random sampling, with the sample size determined via G*Power using a medium effect size. Data collection utilized validated and reliable subjective well-being and social support scales. Data analysis included assumption tests (normality and linearity) and hypothesis testing with simple regression and Spearman correlation. The findings reveal that social support significantly influences subjective well-being, indicating that higher social support corresponds to greater well-being levels. This highlights the importance of developing social support programs in universities to enhance student well-being. Future research could broaden the scope by involving students from diverse universities and incorporating additional variables, such as self-efficacy or coping strategies, to deepen insights into factors influencing subjective well-being.